Implementing the HACCP system to the production of Bakso Malang-Indonesia. Issue 4 (4th July 2019) - Rifqie Mariana, Rina; Hidayati, Laili; Soekopitojo, Soenar
ABSTRACT: This study aimed to perform hazard analysis based on the HACCP principles on the meatball production of a popular bakso restaurant in Malang City that has had 200 franchises spread in 15 provinces in Indonesia. This analysis was conducted to control the potential biological, chemical, and physical hazards in every stage of the manufacturing chain, from production to serving to consumers. Data were collected through survey and close observation into the production kitchen. The HACCP steps performed were the identification of hazards, determination of CCPs, setting of critical limits, and formulation of corrective actions. The results showed that the phases considered as critical control points are the raw material receipt, meatball shaping by hand, meatball draining, storage, distribution, and serving. The major hazard identified in each process is the growth of pathogens.